2014
DOI: 10.1097/qad.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class I restricted CD8+ and Class II restricted CD4+ T cells are implicated in the pathogenesis of nevirapine hypersensitivity

Abstract: The association of specific class I and II allele pairings with specific phenotypes of NVP HSR, and cellular studies showing both CD4 and CD8 T-cell NVP-specific responses suggest that specific combinations of NVP reactive class I restricted CD8 and class II restricted CD4 T cells contribute to the immunopathogenesis of NVP HSR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…21,22 Future validation of ex vivo T-cell enzyme-linked immunospot assays, which have primarily been explored in antiretroviral hypersensitivity, 23,24 may allow assignment of drug causality whilst avoiding in vivo testing, which is both contraindicated and potentially unhelpful in acute SJS/TEN/ DRESS. [23][24][25][26] Multidisciplinary approaches that include detailed clinical appraisal, ADR Committee review, utilization of SJS/ TEN scoring systems (eg, ALDEN), in vivo skin testing, and ex vivo assays are required to ensure accurate causality assessments.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Future validation of ex vivo T-cell enzyme-linked immunospot assays, which have primarily been explored in antiretroviral hypersensitivity, 23,24 may allow assignment of drug causality whilst avoiding in vivo testing, which is both contraindicated and potentially unhelpful in acute SJS/TEN/ DRESS. [23][24][25][26] Multidisciplinary approaches that include detailed clinical appraisal, ADR Committee review, utilization of SJS/ TEN scoring systems (eg, ALDEN), in vivo skin testing, and ex vivo assays are required to ensure accurate causality assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies investigated both MHC class I and class II alleles [10,[13][14][15][16][17][18]20,21], whereas four studies genotyped specific alleles based on previously published reports [12,19,22,28]. Only a minority of studies reported quality checks for genotyping (three out of 12 studies [14,19,28]).…”
Section: Hla Genotyping Datamentioning
confidence: 92%
“…Of the six studies investigating associations in mixed populations [10,[14][15][16]21,28], four studies classified the population according to the ethnicity of the majority of patients. One study investigated the associations in a mixed population of White and Asians [15], whereas the study by Yuan et al [14] defined different subpopulations in which subgroup-specific analyses were performed.…”
Section: Population and Outcome Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevirapine DDAR appears to be mediated both by CD8+ and CD4+ T cells (which can explain its association with both MHC class I and II molecules) [22,66], and adverse reactions are more common and more severe in immunologically uncompromised patients undergoing HIV postexposure prophylaxis [67]. The risk of severe allergy is higher among patients with a CD4+ count >250 cells/μl (for females) or >400 cells/μl (for males).…”
Section: Nevirapinementioning
confidence: 99%